Protective role of carboxyhemoglobin (COHb) in brain cells - Carrola, André Ramos (2023)
Carboxyhemoglobin (COHb) is a molecule naturally formed in the human body due to hemoglobin scavenge by carbon monoxide. Usually, it is an unwanted molecule due to its neg- ative association as a biomarker of carbon monoxide poisoning. Nevertheless, in recent years, a potential biological protective role of carboxyhemoglobin has been hypothesized as many studies point to the fact that this molecule may not be toxic. Moreover, the conditions for COHb formation may indicate a protective role in human physiology. In this work, the biological role of COHb was assessed in brain cells, as neurodegenerative diseases and stroke are one of the leading causes of death and neurological disability world- wide. Microglial cell line, neuronal-like cell line and a blood brain barrier endothelial cell line were the used models to assess the effects of COHb on neuroinflammation, cell viability and blood brain barrier permeabilization, respectively. Under hemorrhagic diseases or normal erythrocytes turnover, hemoglobin can be released from inside the red blood cells into the bloodstream. Cell-free Hb is rapidly oxidized, forming methemoglobin (MetHb), which is a strong prooxidant molecule. In this work, COHb demonstrated promising results by limiting MetHb-induced inflam- mation in microglial cells. In neurons, COHb does not promote cell death in contrast to MetHb. No conclusive results were obtained whenever the blood brain barrier endothelial cell line model was tested with COHb and MetHb. Although promising results were achieved, the rep- etition of the blood brain barrier model is necessary to achieve conclusive results concerning the biological role of COHb on barrier permeabilization. Further research about this molecule impact, in both human physiological and pathological conditions, is needed to fully understand its biological role.